Caries status and salivary characteristics of South Indian school children with molar incisor hypomineralization: A cross-sectional study - Allwyn Samuel; Sharath Asokan; P R Geethapriya (Wolters Kluwer Medknow Publications, 2017)
Introduction: Molar incisor hypomineralization (MIH) is a common developmental condition resulting in enamel defects in first permanent molars and permanent incisors. Aims: This study aims to determine the prevalence of MIH in school children aged 8-12 years in Tiruchengode, Tamil Nadu, South India. The caries status and the salivary characteristics of children with and without MIH were compared. Materials and Methods: In this cross-sectional study, a total of 4495 children were screened. Children with hypomineralized permanent molars and incisors were diagnosed using the European Academy of Pediatric Dentistry criteria. The caries severity was assessed using the International Caries Detection Assessment System II scoring criteria. The saliva and plaque samples of 50 children with MIH and 50 children with molar hypomineralization (MH) children were collected in a sterile container. Similarly, saliva and plaque sample of the 100 children with no caries and no MIH (control group) were collected and compared with the MIH/MH children. Salivary pH, buffering capacity, and plaque pH were estimated. The data were subjected to statistical analysis using the SPSS software version 17.0. Pearson and Student's t-test were used to compare the data. P =0.05 or less was considered to be of statistical significance. Results: The prevalence of MIH/MH was 5.25% (n = 236) in Tiruchengode district. Among the children, 3.33% (n = 150) boys and 1.91% (n = 86) girls had MIH/MH. The prevalence of dental caries in children with MIH/MH was 52.1% (n = 123 children). Conclusion: MIH is an important clinical problem that often concerns both the general dentists and pediatric dentists. Creating awareness about this condition, early diagnosis, and prompt treatment among the dentists, and population is obligatory, especially in countries like India.